Distribution of IgG subclasses in membranous nephropathy. - Doi, T (1984)
The distribution of human IgG subclasses among the glomerular deposits in human membranous nephropathy was examined by immunofluorescence with subclass specific monoclonal antibodies. Large amounts of granular deposits of IgG4 were identified along the capillary loops in all 12 patients, and seven patients had small amounts of IgG1 deposits. Neither IgG2 nor IgG3 deposits were detectable in any of the patients. On the contrary, all four IgG subclasses were detected in membranoproliferative glomerulonephritis and lupus nephritis with a predominance of IgG1 and IgG3. The results indicate that IgG4 is predominant in the glomerular deposits in membranous nephropathy and may play an important role in its pathogenesis.